If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(x+4)=x+(x+2)+(x+4)-2
We move all terms to the left:
(x+4)-(x+(x+2)+(x+4)-2)=0
We get rid of parentheses
x-(x+(x+2)+(x+4)-2)+4=0
We calculate terms in parentheses: -(x+(x+2)+(x+4)-2), so:We get rid of parentheses
x+(x+2)+(x+4)-2
We get rid of parentheses
x+x+x+2+4-2
We add all the numbers together, and all the variables
3x+4
Back to the equation:
-(3x+4)
x-3x-4+4=0
We add all the numbers together, and all the variables
-2x=0
x=0/-2
x=0
| 1/3=m+1/4 | | 2.5t+7.7=4.7 | | 2.5t+4.7=7.7 | | 7/8x-9/16=-1/2 | | 3y-7+y+47=5y+40-3y | | (x+1)=2x+15 | | x=3(-x)+68 | | 6-8y=70 | | 3+2(8x-9)=5x-26 | | 6-8y=80 | | 6=x/4+9 | | 2n^2+n=300 | | −4.75=z/2 | | 2.71^4x=20 | | 6k+k+14=56 | | -6=2g | | 6d+4=15 | | 900x=2580 | | -7(v+3)=21 | | -12=3c | | -2=-3-p | | -41=8y-1 | | (3t)(3t)-3t+1=0 | | 4=-j | | -3=-q | | 6=5-j | | 2=2+3v | | -2+u/2=2 | | 9=7+r/5 | | -4=a/5-9 | | C-12=4-3c | | j-4j-12j=12 |